The Effect of Anredera cordifolia Extract towards Kidney Histopathological Features on Cyprinus carpio Infected by Aeromonas hydrophila - Noor, Huriyatul Fitriyah; Weargo Jati, Ciptaning; Putriani, Rizha Bery (Badan Penerbitan Fakultas Pertanian (BPFP), 2024)
Favoured by Indonesian citizens, Cyprinus carpio production decreased over time due to diseases caused by Aeromonas hydrophila in the aquaculture process. Antibiotics are often used to manage the disease on media, but they could cause resistance to the bacteria. Herbs were used as the alternative for these antibiotics. This experiment aimed to find the effect of Anredera cardifolia extract on the kidney histopathology of C. carpio infected by A. hydrophila. The dosage used in this experiment was 200ppm, 400ppm, and 600ppm for each treatment with three repetitions. There was also negative and positive control. The bacteria density used for the positive control was 107 cells/ml. After infection, kidney tissue was taken three days post-recovery. Descriptive analysis was used to analyse the kidney histopathology, while to determine the level of the damage carried out by the bacteria, we used the scoring level. This research showed that treating A. cordifolia affects the kidney histopathology of C. carpio infected by Aeromonas. The damaged tissue found was necrosis, edema, and congestion. The best dose used to improve the damaged kidney tissue on C. carpio was treatment B (400ppm), indicated by the scoring results for minor damage; the structure showed the tissue figure looked similar to the normal tissue.